IRE1, a component of the unfolded protein response signaling pathway, protects pollen development in Arabidopsis from heat stress. (26th August 2016) - Deng, Yan; Srivastava, Renu; Quilichini, Teagen D.; Dong, Haili; Bao, Yan; Horner, Harry T.; Howell, Stephen H.
Summary: The unfolded protein response (UPR) is activated by various stresses during vegetative development in Arabidopsis, but is constitutively active in anthers of unstressed plants. To understand the role of the UPR during reproductive development, we analyzed a double mutant, ire1a ire1b . The double mutant knocks out the RNA‐splicing arm of the UPR signaling pathway. It is fertile at room temperature but male sterile at modestly elevated temperature (ET). The conditional male sterility in the mutant is a sporophytic trait, and when the double mutant was grown at ET, defects appeared in the structure of the tapetum. As a result, the tapetum in the double mutant failed to properly deposit the pollen coat at ET, which made pollen grains clump and prevented their normal dispersal. IRE1 is a dual protein kinase/ribonuclease involved in the splicing of bZIP60 mRNA, and through complementation analysis of various mutant forms of IRE1b it was demonstrated that the ribonuclease activity of IRE1 was required for protecting male fertility from ET. It was also found that overexpression of SEC31A rescued the conditional male sterility in the double mutant. SEC31A is involved in trafficking from the endoplasmic reticulum to Golgi and a major target of the IRE1‐mediated UPR signaling in stressed seedlings. Thus, IRE1, a major component of the UPR, plays an important role in protecting pollen development from ET. Significance Statement: The Unfolded Protein Response (UPR) in plants is activated by various environmental stresses during vegetative development, but is constitutively active in flowers. Here we show that a major component of the UPR signaling pathway, IRE1, a dual protein kinase/ribonuclease, protects plant reproduction, the most vulnerable stage in a plant's life cycle and that the ribonuclease function of IRE1 was critical for this protection. The ire1 mutant is male sterile at elevated temperatures because the tapetum in its anthers fails to properly deposit the pollen coat.